2002
DOI: 10.1006/mthe.2002.0805
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a Splicing Defect in Erythroid Cells from Patients with β-Thalassemia/HbE Disorder

Abstract: A HeLa cell line stably expressing the human beta-globin gene carrying thalassemic mutations beta(E)/IVS1-6 served as a thalassemia model for repair of aberrant splicing of beta(E)-globin pre-mRNA with antisense oligonucleotides. Treatment of beta(E)/IVS1-6 HeLa cells with a morpholino oligonucleotide targeted immediately upstream of the aberrant 5' splice site activated by the mutations resulted in an increase in the amount of correctly spliced beta(E)-globin mRNA in a dose-dependent and sequence-specific fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…1 For instance, AONs have restored normal splicing by blocking cryptic splice sites, 2,3 altered the ratio of alternative splicing from malignant to nonmalignant isoforms, 4 and induced exon inclusion for mutated exons that were otherwise skipped. 5 In these studies, the AON treatments aimed at the re-establishment of wild-type mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…1 For instance, AONs have restored normal splicing by blocking cryptic splice sites, 2,3 altered the ratio of alternative splicing from malignant to nonmalignant isoforms, 4 and induced exon inclusion for mutated exons that were otherwise skipped. 5 In these studies, the AON treatments aimed at the re-establishment of wild-type mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Work in this laboratory showed that splice-switching oligonucleotides (SSOs), which block aberrant splice sites in IVS2-654 and other pre-mRNAs (IVS1-5, IVS1-6, IVS1-110, IVS2-705, and IVS2-745) as well as in the coding sequence (HbE) of the ␤-globin gene, force the splicing machinery to reselect the existing correct splice sites, repairing the splicing pattern of ␤-globin pre-mRNA. This repair, which restores production of correctly spliced ␤-globin mRNA and protein, was accomplished in several in vitro systems and ex vivo in erythroid progenitor cells from thalassemic patients (6)(7)(8)(9)(10)(11)(12). In this study, we investigated the effectiveness in thalassemic splicing correction of a modified morpholino oligomer, SSO 654-P005, in a mouse model of IVS2-654 ␤-thalassemia.…”
mentioning
confidence: 99%
“…Antisense oligonucleotides have been used to restore pre-mRNA splicing in other disease models (1)(2)(3)(4)(5)(6)(7)(8); however, the therapeutic rationale for each varies considerably and, to our knowledge, none has addressed an intranuclear or DNA repair disorder. Furthermore, we believe that A-T offers several advantages for exploring the therapeutic potential of AMOs, such as (i) the availability of many surrogate markers for evaluating ATM function, ex vivo and in vivo, and (ii) a well characterized spectrum of ATM mutations supported by an extensive cell repository of lymphoblastoid cell lines (LCLs) derived from patients with those mutations (9)(10)(11)(12).…”
mentioning
confidence: 99%